2011
DOI: 10.1002/jso.21915
|View full text |Cite
|
Sign up to set email alerts
|

A role for CD95 signaling in ischemia/reperfusion‐induced invasion and outgrowth of colorectal micrometastases in mouse liver

Abstract: I/R induces invasion and accelerated outgrowth of preestablished metastases in a CD95-dependent manner. Activation of the CD95 system following I/R not only contributes to liver injury, but may also promote aggressive tumor recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Enhanced in vitro invasion after CD95L stimulation was also observed for oncogenic KRAS‐expressing DLD1 cells and was found to be independent from caspase‐8 activation . Moreover, accelerated CD95‐mediated outgrowth of C26 micrometastases in the liver has also been observed after radiofrequency ablation and induction of ischemia‐reperfusion ischemia . The underlying CD95 signaling mechanisms have not been addressed in these studies but a follow‐up in vitro study demonstrated that CD95 signals tumor cell invasion in a transwell assay by Src kinase family‐independent activation of the PDGFRβ and subsequent PDGFRβ‐dependent PLCγ1 stimulation (Fig.…”
Section: Cell Migration and Invasion Can Be Induced By Several Cd95‐ mentioning
confidence: 99%
“…Enhanced in vitro invasion after CD95L stimulation was also observed for oncogenic KRAS‐expressing DLD1 cells and was found to be independent from caspase‐8 activation . Moreover, accelerated CD95‐mediated outgrowth of C26 micrometastases in the liver has also been observed after radiofrequency ablation and induction of ischemia‐reperfusion ischemia . The underlying CD95 signaling mechanisms have not been addressed in these studies but a follow‐up in vitro study demonstrated that CD95 signals tumor cell invasion in a transwell assay by Src kinase family‐independent activation of the PDGFRβ and subsequent PDGFRβ‐dependent PLCγ1 stimulation (Fig.…”
Section: Cell Migration and Invasion Can Be Induced By Several Cd95‐ mentioning
confidence: 99%
“…5 However, under certain conditions, Fas signaling can exert non-apoptotic effects, including inflammatory responses, liver regeneration, increased branching of developing neurons, migration of cells, angiogenesis, fibrosis, proliferation and differentiation of cells and advancement of the cell cycle. [6][7][8][9][10][11] Therefore, although almost all tumor cells express the Fas receptor, the Fas pathway may also be beneficial to tumor cell survival rather than apoptosis. 6,[8][9][10] Activation of Fas signaling in the Lewis lung cancer cell line (3LL cells) does not cause apoptosis but induces 3LL cells to secrete more prostaglandin E2(PGE2).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Therefore, although almost all tumor cells express the Fas receptor, the Fas pathway may also be beneficial to tumor cell survival rather than apoptosis. 6,[8][9][10] Activation of Fas signaling in the Lewis lung cancer cell line (3LL cells) does not cause apoptosis but induces 3LL cells to secrete more prostaglandin E2(PGE2). 12 High levels of PGE2 aid 3LL cells in recruiting myeloid-derived suppressor cells (MDSCs), leading to tumor cell escape.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we have previously shown that the presence of oncogenic KRAS in colon cancer cells causes a switch in CD95-signaling output from apoptosis to invasion, which is required for metastatic spread and tumor recurrence. 15, 20, 21 This raises the question of how to select patients for CD95-inhibitory therapy and whether there could be genetic or epigenetic traits that may determine the response to such therapy. To address this, we further explored the context dependency of CD95 signaling in human colon cancer by making use of a series of patient-derived ‘colonosphere' cultures.…”
mentioning
confidence: 99%